Semi-empirical model for estimating the heat release rate required for flashover in compartments with thermally-thin boundaries and ultra-fast fires. (March 2021) - Beshir, M.; Wang, Y.; Centeno, F.; Hadden, R.; Welch, S.; Rush, D.
Abstract: More than 1 billion people are living in informal settlements and refugee camps where houses are commonly built from thermally-thin materials (e.g. steel/asbestos sheets). In fire safety literature there is insufficient attention describing the required conditions for flashover (e.g. Heat Release Rate needed for flashover Q ˙ F O ) in such compartments. In this work, Q ˙ F O and heat fluxes to the surroundings for compartments with thermally-thin boundaries were investigated using eight compartment fire tests built with 0.5 mm steel sheets and four fuel loads. Numerical simulations were conducted to validate FDS for this application, using the heat release rate inside and outside the compartment, the gas layer temperature and the heat fluxes to the surroundings. The validated model was employed to conduct demonstrative sensitivity and parametric studies to understand the heat balance for thermally-thin under-ventilated compartments. It was found that the heat transfer on/from the walls of the compartment is dominated by radiation, in contrast to the compartments with thermally thick boundaries where the wall conduction dominates. The radiative heat transfer coefficient h rad was then resolved numerically and correlated against the gas layer temperature, wall temperatures and the Q ˙ F O to create a semi empirical correlation for estimating the Q ˙ F O . Highlights: Thermally thin small scale compartment tests conducted with 4 different fuel loads. FDS model validated for small scale under ventilated compartment fire. Numerical parametric study: ventilation effect and wall's thermal properties. An empirical correlation for Q ˙ F O for thermally thin compartments was generated. Sensitivity analysis: main heat transfer parameters for thermally thick/thin walls.